Reassessing Productivity in the Digital Age: The Impact of Social Media Addiction and Job Stress - Gunawan, Nadia Khairani; Hakim, Abdurrahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This research departs from the high usage of social media among Generation Z in Indonesia. The objective of this research is to identify the effects of social media addiction and job stress on the work productivity of Generation Z. Design/methodology/approach – This quantitative explanatory study involved 239 Generation Z employees across Indonesia, selected using a convenience sampling method. Data were collected using Likert-scaled questionnaires and analyzed with PLS-SEM in SmartPLS 3.0 to assess the measurement model, structural model, and overall model fit. Findings – The results show that social media addiction has a significant negative effect on work productivity, while job stress does not have a significant direct impact. Interestingly, mild stress conditions are perceived by respondents as a motivational factor that can enhance productivity. Originality/value – This study provides new empirical evidence on the influence of social media addiction and job stress on the productivity of Generation Z employees in Indonesia. It offers a generational and contextual perspective from a developing country, highlighting how digital behavior and workplace dynamics shape modern employee performance.